1994
DOI: 10.3109/03009749409103063
|View full text |Cite
|
Sign up to set email alerts
|

Double Blind Radiological Assessment of Continuous Oral Pamidronic Acid in Patients with Rheumatoid Arthritis

Abstract: Continuous oral pamidronate (APD), 1000 mg/day, was administered to 14 patients with rheumatoid arthritis. A control group of 13 patients with similar conditions received placebo under a double blind randomized study design. Periarticular erosion scores were significantly higher in the control group after 12 months treatment. This was attributed to a deterioration in this group rather than to an improvement in the APD treated one. By contrast, intraarticular narrowing score was not influenced by APD. Tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
1
3

Year Published

1996
1996
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 12 publications
0
22
1
3
Order By: Relevance
“…Therefore, the contrast between the sup- AA, adjuvant-induced arthritis; CA, collagen-induced arthritis; RA, rheumatoid arthritis; E, effective; NE, not effective; W, worsening. References: (1) Francis et al, 1972;(2) Flora, 1979;(3) Babier et al, 1986;(4) Francis et al, 1989;(5) Nugent et al, 1993;(6) Dunn et al, 1993a;(7) Markusse et al, 1990;(8) Ralston et al, 1989;(9) Tan et al, 1989;(10) Bijvoet et al, 1980;(11) Maccagno et al, 1994; (12) present results. pressive effect of non-aminoBPs and the ineffectiveness of aminoBPs on arthritis cannot be attributable to effects on bone resorption.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Therefore, the contrast between the sup- AA, adjuvant-induced arthritis; CA, collagen-induced arthritis; RA, rheumatoid arthritis; E, effective; NE, not effective; W, worsening. References: (1) Francis et al, 1972;(2) Flora, 1979;(3) Babier et al, 1986;(4) Francis et al, 1989;(5) Nugent et al, 1993;(6) Dunn et al, 1993a;(7) Markusse et al, 1990;(8) Ralston et al, 1989;(9) Tan et al, 1989;(10) Bijvoet et al, 1980;(11) Maccagno et al, 1994; (12) present results. pressive effect of non-aminoBPs and the ineffectiveness of aminoBPs on arthritis cannot be attributable to effects on bone resorption.…”
Section: Discussionmentioning
confidence: 72%
“…These results seem to be in agreement with those of our animal experiments. On the other hand, Bijvoet et al (1980) andMaccagno et al (1994) reported AHPrBP was effective in suppressing rheumatoid arthritis. By way of an explanation for this discrepancy, Maccagno et al (1994) pointed out differences between the groups in terms of dose and period of administration.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of bisphosphonates in RA generally demonstrated suppressive effects on generalized bone loss but not on focal bone erosions (43)(44)(45)(46). In fact, protection against structural joint damage was reported only with high-dose pamidronate (44).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, protection against structural joint damage was reported only with high-dose pamidronate (44). Factors such as the absence of an extensive bone surface at the joint, lack of drug potency, or underdosing may explain why clinical trials of bisphosphonates have thus far failed to demonstrate modification of structural joint damage (47).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous trials in patients with RA have demonstrated the beneficial effects of oral or parental bisphosphonates in preventing the progression of generalized skeletal bone loss and stabilizing systemic bone mass. Despite their success in preventing systemic bone loss, however, trials with bisphosphonates in patients with RA have not demonstrated efficacy with respect to attenuating the progression of focal bone erosions (6)(7)(8)(9)(10). In contrast, results of studies in several different animal models of inflammatory arthritis indicate that bisphosphonate treatment can produce beneficial effects in both systemic bone loss and progression of focal bone erosions (3,(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%